Évaluation d’une programme de développement vocationnel pour les adolescentes (Vire-Vie) - Riverin-Simard, Danielle (Canadian Journal of Counselling and Psychotherapy, 2012)
In the framework of a broad study directed at the evaluation of a vocational development program for adolescents (Wheel of Fortune) it was hoped to confirm, among other things, the effect of this program in terms of education in the work values. The Perron and Dupont Work Values questionnaire was used. Analysis of covariance indicated that after eight weeks (p <.01 ) and after one year (p <.05) the subjects of the experimental groups, when compared to the control groups, showed a positive and significant increase with respect to the values on one of the five scales, the climate variable. The authors conclude that the Wheel of Fortune program seems to, among other positive results, have an educational effect on the work values as far as the "Climate" scale is concerned.